Slavic idea in political thought of underground Poland during World War II = Idea słowiańska w myśli politycznej Polski podziemnej w czasie II wojny światowej - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
After the German invasion in 1941, the USSR declared to be the defender of the Slavic nations occupied by Germany. It did not defend their allies, Czechoslovakia and Yugoslavia, against the Germans in the 1938-1941. In alliance with Germans it attacked Poland in 1939. Soviets used the Slavic idea to organize armed resistance in occupied nations.
Keywords: Slavic idea; Slavic nations; Polish-Soviet relations; idea słowiańska; narody słowiańskie; stosunki polsko-radzieckie